2020
DOI: 10.1186/s12955-020-01503-z
|View full text |Cite
|
Sign up to set email alerts
|

Burden of Care in Caregivers of Iranian patients with chronic disorders: a systematic review and meta-analysis

Abstract: Introduction: Caring for patients with chronic disorders can lead to different problems for caregivers in physical, psychological, social, family, and financial domains. High levels of burden of care can make caregivers vulnerable to physical and psychological conditions and influence their quality of life. Therefore, the goal of the present study was to estimate the overall percentage of burden of care in caregivers of Iranian patients with chronic disorders. Methods: A total of 25 articles published from inc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
30
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(31 citation statements)
references
References 49 publications
0
30
1
Order By: Relevance
“…Care burden has a substantial effect on caregivers' health. Many studies showed that informal home caregivers have a high health risk for burden, stress, depression, irritability, and aggression, and these health problems were associated with a variety of health complications during caregiving [38,39]. In a study conducted by Schulz and Beach [40], individuals who care for their spouses at an older age were compared in a 4-year cohort study.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Care burden has a substantial effect on caregivers' health. Many studies showed that informal home caregivers have a high health risk for burden, stress, depression, irritability, and aggression, and these health problems were associated with a variety of health complications during caregiving [38,39]. In a study conducted by Schulz and Beach [40], individuals who care for their spouses at an older age were compared in a 4-year cohort study.…”
Section: Discussionmentioning
confidence: 99%
“…Each of the statements is answered using a Likert-type scale, with scores ranging from 0 to 4 (never, rarely, sometimes, quite frequently, and nearly always). The composite score was then calculated, and the burden was graded as follows: little or no burden (≤20), mild burden (21)(22)(23)(24)(25)(26)(27)(28)(29)(30)(31)(32)(33)(34)(35)(36)(37)(38)(39)(40), moderate to severe burden (41-60), and severe burden (>61-88). The ZCBS has good internal consistency reliability, with a Cronbach's alpha coefficient of .92.…”
Section: Methodsmentioning
confidence: 99%
“…There are many studies showing that informal home caregivers have a high health risk for burden, stress, depression, irritability, aggression and these health problems leads variety of health complications during caregiving. [38,39] In a study conducted by Schulz and Beach [40], individuals who care for their spouses at an older age were compared in a 4-year cohort study. It was found that the mortality risk of individuals who care for their spouse and feel the burden of care is 63% higher than those who do not need to care for their spouse.…”
Section: Discussionmentioning
confidence: 99%
“…Each of the statements is answered using a Likert-type scale, with scores ranging from 0 to 4 (never, rarely, sometimes, quite frequently, and nearly always). The composite score was then calculated, and the burden was graded as follows: little or no burden (≤20), mild burden (21)(22)(23)(24)(25)(26)(27)(28)(29)(30)(31)(32)(33)(34)(35)(36)(37)(38)(39)(40), moderate to severe burden (41-60), and severe burden (>61-88). The ZCBS has good internal consistency reliability, with a Cronbach's alpha coefficient of 0.92.…”
Section: Methodsmentioning
confidence: 99%
“…For caregivers of cancer patients, caregiver burden was heavier for those who were younger, male, single, and with primary school education or below. In this setting, the burdens of family caregiving may include not only physical tasks but also emotional distress, since caregivers tend to neglect their own needs on behalf of the patient (Rezaei et al, 2020). An obvious signs and symptoms of family caregiving stress and burden of care are often psychological problems; most commonly anxiety, depression, irritability feeling tired and run down, difficulty sleeping, overreacting to minor problems, new or worsening health problems, trouble concentrating feeling, smoking, or eating more (World Health Organization, 2021).…”
Section: Introductionmentioning
confidence: 99%